The Janus-Face of Language: Where Are the Emotions in Words and the Words in Emotions? - Peter Walla (Frontiers Research Topics, 2018)
Language has long been considered independent from emotions. In the last few years however research has accumulated empirical evidence against this theoretical belief of a purely cognitive-based foundation of language. In particular, through research on emotional word processing it has been shown, that processing of emotional words activates emotional brain structures, elicits emotional facial expressions and modulates action tendencies of approach and avoidance, probably in a similar manner as processing of non-verbal emotional stimuli does. In addition, it has been shown that emotional content is already processed in the visual cortex in a facilitated manner which suggests that processing of emotional language content is able to circumvent in-depth semantic analysis. Yet, this is only one side of the coin. Very recent research putting words into context suggests that language may also construe emotions and that by studying word processing one can provide a window to one's own feelings. All in all, the empirical observations support the thesis of a close relationship between language and emotions at the level of word meaning as a specific evolutionary achievement of the human species. As such, this relationship seems to be different from the one between emotions and speech, where emotional meaning is conveyed by nonverbal features of the voice. But what does this relationship between written words and emotions theoretically imply for the processing of emotional information? The present Research Topic and its related articles aim to provide answers to this question. This book comprises several experimental studies investigating the brain structures and the time course of emotional word processing. Included are studies examining the affective core dimensions underlying affective word processing and studies that show how these basic affective dimensions influence word processing in general as well as the interaction between words, feelings and (expressive) behavior. In addition, new impetus comes from studies that on the one hand investigate how task-, sublexical and intrapersonal factors influence emotional word processing and on the other hand extend emotional word processing to the domains of social context and self-related processing. Finally, future perspectives are outlined including research on emotion and language acquisition, culture and multilingualism. In summary, this textbook offers scientists from different disciplines insight into the neurophysiological, behavioral and subjective mechanisms underlying emotion and language interactions. It gives new impulses to existing theories on the embodiment of language and emotion and provides new ways of looking at emotion-cognition interactions.